Brachioradial pruritus: Mayo Clinic experience over the past decade. (31st October 2013) - Mirzoyev, S.A.; Davis, M.D.P.
Abstract : What's already known about this topic? Brachioradial pruritus (BRP) is a fascinating condition that is seen increasingly often. Additional data from retrospective observational studies could enhance our understanding of the disease. What does this study add? This study reports data on a large number of patients with BRP. We add to the limited knowledge of BRP, and we hope that the experience at our institution will provide guidance in diagnosing and managing this medical condition. Summary: Background: Brachioradial pruritus (BRP) is a fascinating condition that is seen increasingly often, but any additional data from retrospective observational studies can still enhance our understanding. Objectives: To review our experience at the Mayo Clinic with patients presenting with BRP. Methods: We retrospectively reviewed the clinical records of patients diagnosed with BRP between 1999 and 2011. Results: In total, 111 patients (80 female, 72%) had been diagnosed with BRP. Their mean age was 59 years, range 12–84 years. Symptoms were bilateral in 84 (75·7%). Fifty‐four patients (48·6%) reported prolonged exposure to the sun, and 16 had a history of neck concerns. Forty‐five (40·5%) had undergone imaging studies of the neck; of these, eight had foraminal stenosis, six had protrusion of the intervertebral disk and six had stenosis of the spinal canal; 10 had more than one cervical abnormality. Thirty‐one patients had been referred to neurology; eight of these had BRP attributed to a radiculopathy or peripheral neuropathy. Several topical and oral medications were prescribed. Seventy‐five patients had a follow‐up; of these, nine (12%) had complete resolution, 13 (17%) had improvement, four (5%) showed no change and 49 (65%) had no mention of BRP. Conclusions: Brachioradial pruritus presented most commonly in female patients and was observed over a wide age range. Although a third of patients with imaging studies had cervical abnormalities, the significance of these findings is unclear, as no structural causes of BRP were found in most cases. Some treatments were more successful than others.